Հայոց ցեղասպանության հրապարակայնացումը Անգլիայում. Ջեյմս Բրայս և Առնոլդ Թոյնբի - Տիգրան Սարուխանյան (ՀՀ ԳԱԱ հրատ.)
Освещение геноцида армян во время Первой мировой войны в Англии было продиктовано официальными интересами этой страны. Выступая как "освободительница малых народов" , Англия оправдывалась перед собственной и мировой общественностью за свое участие в Первой мировой войне. The enlightenment of the Armenian Genocide in England, during World War I, was due to the national interests of Great Britain. Presenting herself as "the liberator of the small nations"; Great Britain tries to explain the international and own public, the reason of her participation in World War I.
Keywords: History; Armenian Genocide (1915); D History